Cover Feature: Synthesis of Unprecedented 4d/4f‐Polypnictogens (Chem. Eur. J. 12/2021). Issue 12 (14th January 2021) - Reinfandt, Niklas; Schoo, Christoph; Dütsch, Luis; Köppe, Ralf; Konchenko, Sergey N.; Scheer, Manfred; Roesky, Peter W.
Abstract : A kind of "street art lab‐journal" on a graffiti wall is depicted in the cover image. The left side shows a table where the already obtained d/f‐polypnictides (P, As) are ticked, while Sb is still marked as an unsolved task. According to this, the right side shows the reaction equation, which represents the pathway to the solution of the task and finally the resulting, artistically highlighted, compound. On the bottom you can see the ′spray cans of the elements′, which are required for this compound. More information can be found in the Communication by P. W. Roesky et al. on page 3974 .